Surveillance of Opioid Prescribing as a Public Health Intervention: Washington State Bree Collaborative Opioid Metrics - Fulton-Kehoe, Deborah (J Public Health Manag Pract, 2020)
CONTEXT: To address risks associated with prescription opioid medications, guidelines recommend lower dose, shorter duration of use, and avoidance of concurrent sedatives. Monitoring opioid-prescribing practices is critical for assessing guideline impact, comparing populations, and targeting interventions to reduce risks. OBJECTIVE: To describe development of Washington (WA) State opioid-prescribing metrics, provide purpose and definitions, and apply metrics to prescription data for WA health care organizations. DESIGN: We describe the development and testing of opioid-prescribing metrics by the WA State Bree Collaborative opioid work group. SETTING: Washington State. PARTICIPANTS: Kaiser Permanente of Washington (KPW) Integrated Group Practice, KPW-contracted care providers, and WA Medicaid. MAIN OUTCOME MEASURES: Set of 6 strategic metrics tested across 3 different health systems adopted by WA State in 2017 for uniform tracking of opioid-prescribing guidelines and state policies. These metrics include (1) overall prevalence of any opioid use, (2) chronic use, (3) high-dose chronic use, (4) concurrent chronic sedative use, (5) days' supply of new prescriptions, and (6) transition from acute to chronic use. RESULTS: In the first quarter of 2010, 10% to 12% of KPW and 14% of Medicaid patients received at least 1 opioid prescription. Among opioid users, 22% to 24% of KPW and 36% of Medicaid patients received chronic opioids. Among patients receiving chronic opioids, 16% to 22% of KPW and 32% of Medicaid patients received high doses (≥90 morphine-equivalent dose per day) and 20% to 23% of KPW and 33% of Medicaid patients received concurrent chronic sedatives. Five percent of Medicaid and 2% to 3% of KPW patients receiving new opioid prescriptions transitioned to chronic opioid use. CONCLUSIONS: The metrics are relatively easy to calculate from electronic health care data and yield meaningful comparisons between populations or health plans. These metrics can be used to display trends over time and to evaluate the impact of opioid-prescribing policy interventions.